(Pre-intermediate; Student's guide) (Hà Nội, 2003)
This book is one of a set of five self-study modules which accompanies the pre-intermadiate Lifelines coursebook and cassettes
Keywords: English language,English language,Listening; Spoken english,Problems, exercises, etc,Textbooks for foreign speakers,Problems, exercises, etc